Vpliv hormonskih kontraceptivov na zmogljivost vzdržljivostnih športnic - Svete, Zala (Šport (Ljubljana), 2024)
Hormonal contraceptives are used by many women worldwide. In addition to their effects on regulating the menstrual cycle and pregnancy, taking these contraceptives may also influence their physical performance. Therefore, we conducted a review to examine the impact of hormonal contraceptive use on performance in female endurance athletes. Due to the high heterogeneity in both the design and results of individual studies, we specifically analysed studies comparing a group taking hormonal contraceptives and a group with regular menstruation; studies comparing results before and after taking hormonal contraceptives; and studies comparing specific measured parameters at different phases of the cycle. Overall, we found trends indicating changes in performance after a prolonged period of hormonal contraceptive use; most evidence points to a decrease in peak oxygen concumption, but the effects are trivial and results between studies are too varied so we cannot speak with certainty about the impact of contraceptive use on athletic performance. Further research is needed for more accurate understanding of the impact of hormonal contraceptives and to provide definitive conclusions.
Keywords: eksogeni hormoni; exogenous hormones; hormonal contraceptives; hormonski kontraceptivi; performance; sport; šport; zmogljivost